Peer Tutoring and Its Impact on Academic Performance in a University Mathematics Course - Chacón-Vargas, Erick (Revista Electrónica Educare, 2022)
Purpose. To analyze the impact of peer tutoring, as part of the academic success program (ASP), on the performance of first-year students enrolled in the General Mathematics course taught at the Technological Institute of Costa Rica (TEC). Method. Data provided by 528 new students from TEC, who enrolled in the ASP during the first half of 2019, were analyzed. The goodness-of-fit tests were used to compare frequency distributions of the grades obtained in the course by the participants and the total population. The same tests were used to determine if the number of tutorials they attended had any incidence on their final condition in the course. Results. The average grade in the General Mathematics course obtained by the students who attended the leveling sessions taught by the ASP during the week before the start of the school year was 5 points above the average mark of the other students. The pass rate of the first ones was almost 5% higher than that of the rest of the first-year students in the course. Conclusions. It was determined that there is no statistically significant difference between the distribution of grades obtained by ASP participants and by the total number of students in the course; however, it is observed that the participants’ average grades tend to be higher according to the number of sessions they attended.